Potential Markers of Progression in Idiopathic Parkinson’s Disease Derived From Assessment of Circular Gait With a Single Body-Fixed-Sensor: A 5 Year Longitudinal Study - Micó-Amigo, M. Encarna; Kingma, Idsart; Heinzel, Sebastian; Rispens, Sietse M.; Heger, Tanja; Nussbaum, Susanne; van Lummel, Rob C.; Berg, Daniela; Maetzler, Walter; van Dieën, Jaap H. (Frontiers in Human Neuroscience, 2019)
Background and aim: Development of objective, reliable and easy-to-use methods to obtain progression markers of Parkinson’s disease (PD) is required to evaluate interventions and to advance research in PD. This study aimed to provide quantitative markers of progression in idiopathic Parkinson’s disease (PD) from the assessment of circular gait (walking in circles) with a single body-fixed inertial sensor placed on the lower back. Methods: The assessments were performed every 6 months over a (up to) 5 years period for 22 patients in early-stage PD, 27 patients in middle-stage PD and 25 healthy controls (HC). Longitudinal changes of 24 gait features extracted from accelerometry were compared between PD groups and HCs with generalized estimating equations analysis, accounting for gait speed, age and levodopa medication state confounders when required. Results: Five gait features indicated progressive worsening in early stages of PD: number of steps, total duration and harmonic ratios calculated from vertical (VT), medio-lateral (ML) and anterior-posterior (AP) accelerations. For middle stages of PD, three gait features were identified as potential progression markers: stride time variability, and stride regularity from VT and AP acceleration. Conclusions: Faster progressive worsening of gait features in both PD groups relative to HC over 5 years confirmed the potential of accelerometry-based assessments as quantitative progression markers in early and middle stages of the disease. The difference in significant parameters between early and mid-stage PD suggests that distinct domains of gait deteriorate in these PD stages. We conclude that instrumented circular walking assessment is a practical and useful tool in the assessment of PD progression that may have relevant potential to be implemented in clinical trials and even clinical routine in a developing digital era.